Analysis of the Application of Politeness Maxims and Cost-benefit in Comment Section LinkedIn - Lira Mey Nisa; Tiodame Layupa Simanullang; Nijmal adawiyah; Octavia Amelia; Nabilah Siti Haniyah; Muhammad Natsir (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study explores the use of Leech's politeness maxims and the cost-benefit principle in LinkedIn comments about job postings, aiming to understand how job seekers maintain politeness when pursuing job opportunities in a professional digital environment. The research objects used were comments in 5 job postings. Using a descriptive qualitative approach, the comments on the LinkedIn platform were analysis and classified based on the 6 maxims proposed by Leech: Tact Maxim, Generosity maxim, Approbation Maxim, Modesty Maxim, Agreement Maxim and Sympathy Maxim. The findings showed that out of a total of 31 data found, the Tact Maxim (32%) was the most common, followed by Approbation Maxim (16%), Generosity maxim (13%), Modesty Maxim (13%), Agreement Maxim (3,2%) and Sympathy Maxim (3,2%). Further cost-benefit analysis revealed that most of the comments showed a lack of politeness, focusing only on personal benefits without providing benefits to the interlocutor.